Resúmenes de novedades - Foro Internacional, Revista (El Colegio de México A.C., 2023)
Joseph MacKay, The Counterinsurgent Imagination: A New Intellectual History, Cambridge, Reino Unido, Cambridge University Press, 2023, 322 pp. Lisa Dellmuth y Jonas Tallberg, Legitimacy Politics: Elite Communication and Public Opinion in Global Governance, Cambridge, Reino Unido, Cambridge University Press, 2023, 250 pp. Niko Kolodny, The Pecking Order: Social Hierarchy as a Philosophical Problem, Cambridge, Massachusetts, Harvard University Press, 2023, 496 pp. Vera Slavtcheva-Petkova, Discussing Trump’s America Online: Digital Commenting in China, Mexico and Russia, Suiza, Springer Nature Switzerland AG, 2023, 247 pp. Gilles Favarel-Garrigues, La verticale de la peur: Ordre et allégeance en Russie poutinienne, París, Editions La Découverte, 2023, 240 pp. Philip Giurlando y Daniel F. Wajner (eds.), Populist Foreign Policy: Regional Perspectives of Populism in the International Scene, Suiza, Springer Nature Switzerland ag, 2023, 290 pp. Pierre Blanc, Géopolitique et climat, París, Presses de Sciences Po, 2023, 248 pp. Christina L. Davis, Discriminatory Clubs: The Geopolitics of International Organizations, Princeton, New Jersey, Princeton University Press, 2023, 472 pp. Merike Blofield, Jennifer Pribble y Cecilia Giambruno, The Politics of Social Protection During Times of Crisis, Cambridge, Reino Unido, Cambridge University Press, 2023, 80 pp. Rodrigo Perera Ramos y Gerardo L. Dorantes y Aguilar, Tuiteando desde el poder. Nuevas tecnologías, viejas estrategias. La comunicación política de Andrés Manuel López Obrador, Ciudad de México, UNAM, Facultad de Ciencias Políticas y Sociales, 2023, 166 pp.